Profile and compliance of recipients of injection depot medroxy progesterone acetate as a contraceptive method in the government tertiary care hospital in Mandya, South Karnataka, India - N., Shilpa M.; M., Shwetha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: The advanced contraceptive devices available nowadays have minimal side effects and utmost efficacy. The use of safe and effective contraception is the need of the hour in India. Inj. Depot medroxy progesterone (DMPA) has been found to provide effective, long acting and reversible contraception in lactating mother and post-abortal patients. Objective of this study was to describe the profile of women utilizing inj. DMPA as a contraceptive, to determine its compliance and to assess the factors affecting discontinuation of inj. DMPA (Anthara) at the government tertiary care institute in Mandya. Methods: The present study was a record-based study of 18 months (January 2018 to June 2019). The records of 266 women who utilized inj. DMPA as contraception in our institution was analysed. Results: It was observed that out of 266 women 48.5% were from age group of 21-25 years and 64.3% were primipara. Most of the women who initiated inj. DMPA (Anthara) were in the lactational period (56.0%). Most common side effect was irregular bleeding (54.8%). Discontinuation rate was 55.6% after first injection and 16.9% after second injection and gradually reduced with subsequent injections. The most common reason for discontinuation was irregular spotting per vagina (53.9%). Conclusions: Inj. DMPA is a safe, effective, long acting contraceptive taken once in three months. Many women in early reproductive age and lactational period are using inj. DMPA (Anthara) for contraception because of its convenience of dosing and is easily made available at government health care centres free of cost and has no effect on lactation. Discontinuation rate can be reduced by proper counselling.